Validation of dynamic [18F]FE-PE2I PET for estimation of relative regional cerebral blood flow: a comparison with [15O]H2O PET - Jakobson Mo, Susanna; Axelsson, Jan; Stiernman, Lars; Riklund, Katrine (EJNMMI research, 2022)
Background Dopamine transporter (DAT) imaging is used in the diagnostic work-up in suspected parkinsonian syndromes and dementia with Lewy bodies but cannot differentiate between these syndromes, and an extra brain imaging examination of the regional cerebral blood flow (rCBF) or glucose metabolism is often needed for differential diagnosis. The requirement of two different imaging examinations is resource-consuming and inconvenient for the patients. Therefore, imaging of both cortical blood flow and DAT imaging with the same radiotracer would be more convenient and cost-effective. The aim of this study was to test whether relative regional cerebral blood flow (rCBF R ) can be measured with the DAT-specific positron emission tomography (PET) tracer [ 18 F]FE-PE2I (FE-PE2I), by validation with cerebral perfusion measured with [ 15 O]H 2 O PET (H 2 O). Methods The rCBF R was quantified by kinetic modeling for FE-PE2I ( R1 ) and H 2 O ( F ). The R1 was calculated using the simplified reference tissue model, and F was calculated with a modified Koopman double-integration method. The linear relationship and intraclass correlation (ICC) between R1 and F were tested in image data derived from 29 patients with recent onset parkinsonism and 30 healthy controls. Results There was a strong linear correlation across all subjects between R1 and F in the frontal, parietal, temporal, cingulate and occipital cortex as well as in the striatum ( r ≥  0.731–0.905, p < 0.001) with a good-to-excellent ICC, ranging from 0.727 to 0.943 ( p < 0.001). Conclusions Our results suggest that FE-PE2I may be used as a proxy for cerebral perfusion, thus potentially serving as a radiotracer for assessment of both DAT availability and rCBF R in one single dynamic scan. This could be valuable in the differential diagnosis of parkinsonian syndromes. Trial registration : EUDRA-CT 2015-003045-26. Registered 23 October 2015 https://www.clinicaltrialsregister.eu/ctr-search/search?query=2015-003045-26